Serología de títulos vacunales de la enfermedad de Gumboro en pollos de carne en granjas del sur del Ecuador - Belitama Román, Sandy Berenice (2023)
The objective of this research paperwork was; to determine the immunological of vaccinogenic antibodies against Gumboro disease in broilers from farms in the provinces of El Oro and Loja. We applied a mixed approach, observational, cross-sectional, cross-sectional study in two phases field and laboratory. We used a non-probabilistic convenience sampling with a population of nine farms. We used twenty blood samples from each farm obtained by wing puncture from randomly selected chickens at a slaughter age of 42 days or older. We detected antibodies employing the IDvet Indirect ELISA technique for sanitary information and applied an epidemiological survey of the sampled farms. We analyzed the results utilizing the SAS statistical program using Chi-square, correlations, and regressions for the relationship of the vaccinal titers with the associated factors. Vaccine antibody titers of the farms sampled presented an overall mean of 8406, with minimum titers of 2498, maximum of 13415, and a CV of 39.2% within the range considered as good (<40%). We control this disease by utilizing vaccines such as immunocomplex, live, vectored, and recombinant, which were applied in the hatchery and during production, being an average of three vaccines, a minimum of two, and a maximum of four. The birds came from commercial hatcheries in the country. We found a statistical difference (p<0.001) for the multi-age factor and a trend (p<0.06) for the presence of other poultry and wild birds. In conclusion, the vaccine titers obtained protect the flocks, which depend on the vaccination program and the characteristics of the vaccine; despite this, in some farms, there is viral circulation or field challenge, so we should review the biosecurity plan. Keywords: Chickens, vaccination, ELISA, antibodies, biosecurity